2012
DOI: 10.1097/sle.0b013e3182470f38
|View full text |Cite
|
Sign up to set email alerts
|

Linear-stapled Versus Circular-stapled Laparoscopic Gastrojejunal Anastomosis in Morbid Obesity

Abstract: This pooled analysis recommends the preferential use of the linear stapling technique over circular stapling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 20 publications
0
28
2
Order By: Relevance
“…The risk of infectious wound complications was significantly higher in the studies by Penna et al [10] (pooled OR = 3.13; 95% CI: 2.27–4.35) and Edholm and Sundbom [3] (OR = 9.7; 95% CI: 6.8–13.9). We also revealed that the risk of wound infection increased with the use of a circular stapler.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The risk of infectious wound complications was significantly higher in the studies by Penna et al [10] (pooled OR = 3.13; 95% CI: 2.27–4.35) and Edholm and Sundbom [3] (OR = 9.7; 95% CI: 6.8–13.9). We also revealed that the risk of wound infection increased with the use of a circular stapler.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the use of a circular stapler significantly increased the risk of postoperative hemorrhage, which has also been commonly reported in other studies. In a meta-analysis of five studies by Penna et al [10], the use of a circular stapler was associated with a 117% greater risk of postoperative bleeding in the pooled analysis (pooled odds ratio (OR) = 2.17; 95% confidence interval (CI): 1.49–3.23). An increased risk of postoperative bleeding was also reported in a more recent study by Edholm and Sundbom [3] (OR = 1.9; 95% CI: 1.2–2.9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in our study, the articles published on HSA by Ahmed [11] and Ruiz de Adana [2] report a GIB incidence of 0.4 %. However, mechanical anastomosis presents a rate of GIB ranging from 1.7 to 8.1 % [9,12]. A meta-analysis on more than 9000 patients shows greater postoperative GIB for CSA than for LSA (p<0.0001).…”
Section: Discussionmentioning
confidence: 93%
“…In our study, there was only one case of anastomotic leakage (0.86 %), in the HSA group, which was resolved with suture of the dehiscence and placement of drainage. The meta-analysis published by Penna et al [12] shows no differences in the incidence of leakage between CSA and LSA. The incidence of anastomotic leakage in the study published by Kravetz et al [15] is 0.9 % (with no significant differences between HSA and CSA).…”
Section: Discussionmentioning
confidence: 95%